2020
DOI: 10.20448/journal.501.2020.71.46.63
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Current Account Fluctuations in West African Monetary Union

Abstract: This study analyzes the sources of current account fluctuations in the West African Monetary Union (WAEMU) economies over the period from 1980 to 2017. It is part of the inter-temporal approach which considers that the dynamics of the current account of a country is influenced by global shocks and transient or permanent domestic shocks. Thus, we developed a three-variable structural autoregressive vector model. This is the international real interest rate that represents the aggregate shock, the ratio of curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Mawejje and Odihambo (2022) provides theoretical insights into the challenges associated with fiscal dominance in a lowinterest-rate environment, emphasising the need for a well-articulated monetary policy framework. This theoretical perspective aligns with the growing recognition of the interplay between fiscal and monetary policies, as highlighted by Diallo and Mendy (2018). Their theoretical exploration of fiscal dominance and inflation expectations posits that coordinating monetary and fiscal policies is imperative for managing inflationary pressures effectively.…”
Section: Theoretical Foundation and Reviewmentioning
confidence: 62%
“…Mawejje and Odihambo (2022) provides theoretical insights into the challenges associated with fiscal dominance in a lowinterest-rate environment, emphasising the need for a well-articulated monetary policy framework. This theoretical perspective aligns with the growing recognition of the interplay between fiscal and monetary policies, as highlighted by Diallo and Mendy (2018). Their theoretical exploration of fiscal dominance and inflation expectations posits that coordinating monetary and fiscal policies is imperative for managing inflationary pressures effectively.…”
Section: Theoretical Foundation and Reviewmentioning
confidence: 62%
“…In light of such findings, the study finds a positive and statistically significant response of primary balance to the public debt ratio which implies that fiscal policy is effective in responding to the rising public debt ratios. Diallo and Mendy (2018) impute the effectiveness of primary balance response to the heavily indebted poor countries and multilateral debt relief initiatives launched by the joint efforts of IMF and World Bank. The initiatives resulted in considerable decline in public debt ratios which resulted in more fiscal space and, thus, more funding available to achieve sustained output growth.…”
Section: Panel Quantile Resultsmentioning
confidence: 99%
“…He explained those puzzles indicating that the consumption‐tilting effect should account for most of the current account variations instead of the consumption‐smoothing motive. Likewise, using a similar three‐SVAR specification to study the West African Monetary Union economies, Diallo (2020) found that the Kano's puzzles holds as well.…”
Section: Introductionmentioning
confidence: 97%
“…One technique to analyze the PVM predictions is building a SVAR specification using Blanchard and Quah (1989)'s identification (BQ) to identify the persistence of the structural shocks. Under this setup, some literature include Kano (2008), Kuo (2015), Ibhagui (2017), Diallo (2020), and Bussiere et al (2021). Kano (2008) employed the basic model with uncertainty to analyze Canada and the UK.…”
Section: Introductionmentioning
confidence: 99%